Hybridization of crime fiction genre forms as a representation of contemporary cultural process - G. O. Krapivnyk (Granì, 2014)
The research is devoted to the consideration of hybridization of crime fiction forms in the contemporary cultural process. The work showed that, from the point of view of the culture development, sophistication of the classical crime fiction formula, hybridization of detective fiction with other fiction genres is a natural process of the strive to vary і diversify, combine genres, styles and means of text presentation (from a hard copy or audio book to video and computer games), which is related to the crisis of the Modernity project epoch, where fiction genres were quite selfsufficient, and the transition to the postmodern (or updated Modern), where the human consciousness is dominated by the processes of simultaneous specialization and combination of various industries, in other words, divergence and convergence. It may be claimed that a detective text as one of the most popular genres in the contemporary information culture, in particular, because it reveals secrets, clarifies vague things and assists in discovering the truth, transforms so that there is a process of detectivization of different text products of the cultural industry. At the same time the very detective formula as a component of various genres becomes a tool for playing and influencing the consciousness of a contemporary person.